Hierarchically structured elastomer for absorption-dominated electromagnetic interference shielding in an ultra-wide band - Li, Xing-Yu; Zhao, Pan-Pan; Han, Lin-Xuan; Deng, Cong (Composites science and technology, 2022)
Flexible electromagnetic interference (EMI) shielding materials with low secondary electromagnetic radiation are urgently required for next-generation precise electronic devices and wearable electronics. However, realizing ultra-low microwave reflectivity and sustaining strong absorption feature in a wide frequency range remains a great challenge. Here, natural rubber-based flexible hierarchical composites were fabricated by combination of honeycomb-like 3D networks with selectively distributed ferro/ferric oxide modified graphene (F@rLG) magnetic particles and densely interconnected conductive networks (RL) with fulfilled multiwall carbon nanotubes (MWCNTs) via latex compounding together with co-vulcanization method. The resulting hierarchical bilayer elastomer has the EMI shielding coefficient of 34.4 dB at RL thickness of 0.18 mm, and achieves minimum electromagnetic wave reflection coefficient of 0.1. Moreover, in almost entire Ku band, over 80% incident electromagnetic waves can be absorbed, indicating its excellent capability in minimizing the secondary electromagnetic pollution. And this double-layered flexible material exhibits excellent stability in EMI shielding performance after the deformation cycles of 500 times. In addition, both the influence of precisely manipulated distribution of nanoparticles on the EMI property and the absorption-dominated approach via coupled layers were investigated in depth. This work paves a way for designing flexible EMI shielding materials with low secondary electromagnetic contamination. [Display omitted]